(untitled) (Journal of Dhaka Medical College, 2011)
Transfusion of blood and blood components, as a specialized modality of patient management, saves millions of lives worldwide. Transfusion Medicine is an integral and indispensable part of the healthcare system now. This topic that has been selected is intended to assist the transfusion physician or other specialist physician in acquiring the sense of responsibility for transfusion services. The section includes best practices in handling and administering blood for transfusion, blood management, risks (infectious and non-infectious diseases) of blood components. This topic has been intended to serve in a manner that this little supplement on the state-of-the-practice will facilitate safe patient transfusions, when transfusions are indicated, or minimize or avoid transfusions as appropriate in institutions of all sizes. The ’four principles’ approach - autonomy, beneficence, non-maleficence, and justice - offers a common, basic moral analytical framework and a common, basic moral language to think about ethical issues in any field of health care services. Key words: Transfusion medicine; blood transfusion services; safe blood transfusion; voluntary blood donation; ethical issues. DOI: 10.3329/jdmc.v19i2.7087 J Dhaka Med Coll. 2010; 19(2) : 144-149